Dimorphic autoantigenic and protective effects of Reg2 peptide in the treatment of diabetic β‐cell loss. Issue 5 (1st March 2019) - Yu, Luting; Li, Xiang; Zhang, Zhiyuan; Du, Pei; Liu, Jun‐Li; Li, Youjie; Yin, Tianqi; Yu, Weihong; Sun, Hao; Wang, Min; Luo, Chen
Abstract : Aims: The potential effect of regenerating (Reg) proteins in the treatment of diabetes has been indicated in the past decade, but the clinical use of Reg proteins requires more advances in translational medicine. In the present study, we produced recombinant regenerating protein 2 (rReg2), to prove its protective effect against streptozocin (STZ)‐induced diabetes in BALB/c mice. Materials and Methods: rReg2 was administrated in STZ‐induced diabetic mice. Blood glucose, body weight, serum insulin and islet β‐cell loss were determined. However, Reg2 has also been reported to serve as an autoantigen that induces autoimmune attacks on islets and aggravates diabetic development in non‐obese diabetic mice. To address this contradiction, complete Freund's adjuvant was injected to generate a model that was hypersensitive to Reg2. In this model, islet CD8 T‐cell infiltration, serum Reg2 antibody and interleukin (IL)‐4 and IL‐10, and splenic CD4+/interferon (IFN)‐γ+ T cells were determined. Results: Direct rReg2 pretreatment preserved islet β‐cell mass against STZ and improved glycaemia, body weight and serum insulin content. The protection against cell death was further confirmed in cultured mouse islets and MIN6 cells. On the other hand, significant elevations of serum Reg2 antibody and splenic CD4+/IFN‐γ+ T cells, and decreases in serum IL‐4 and IL‐10 were detected in rReg2‐vaccinated mice, which may contribute to the accelerated diabetes. Interestingly, these mice, upon further rReg2 treatment, exhibited alleviated diabetic conditions with less islet CD8+ T‐cell infiltration. Conclusion: rReg2 treatment ameliorated STZ‐induced diabetes in normal BALB/c mice. By contrast, rReg2 vaccination exacerbated, but further rReg2 treatment alleviated, the severity of STZ‐induced diabetes. Thus, the protective effect of rReg2 is predominant over the autoantigenic β‐cell destruction, supporting the potential of rReg2 in the clinical treatment of diabetes.